Predictors of Length of Stay in Dengue Fever: A Multicenter Study - Khoiruddin, Mukhammad Arif Hadi; Okaniawan, Putu Enrico Pramana; Suarlin, Ketut Ayu Oktavyanti; Nugrah, Putu Arya; Suciawan, Nyoman (Green Publisher Indonesia, 2025)
Dengue fever (DF) is mostly common in certain geographical areas, such as Indonesia, where it continues to be public health problem due to its nature as a viral infection spread through mosquitos. The focus of this study is to assess the factors affecting length of hospital stay (LOS) among DF patients in Buleleng Regency. Between July and December 2024, a cross-sectional investigation was carried out at many hospitals, retrieving the medical records of 940 DF patients. The Spearman test was used in statistical analysis to examine the association between LOS and clinical indicators. The majority of patients (60.96%) were youngsters, 95.5% were admitted to the paediatric ward, and their recovery rate (99.89%) and mortality rate (0.11%) were also high. LOS was significantly associated with leukocyte levels, fever duration, and severity of the disease (p<0.05). However, age, gender, hematocrit, and platelet levels did not show significant association with LOS (p>0.05). This reveals that leukocyte count, duration of fever, and severity of DF contribute in determining hospital stay duration while discharge criteria as such degree of anemia and thrombocytopenia do not appear to be reliable predictors. It is suggested that there is a gap in literature that needs to be looked into regarding the genetic clinical determinants of LOS patients with DF needs further evaluation.